2020
DOI: 10.1186/s13046-020-01669-w
|View full text |Cite
|
Sign up to set email alerts
|

Aspartate β-hydroxylase as a target for cancer therapy

Abstract: As metastasis is a major cause of death in cancer patients, new anti-metastatic strategies are needed to improve cancer therapy outcomes. Numerous pathways have been shown to contribute to migration and invasion of malignant tumors. Aspartate β-hydroxylase (ASPH) is a key player in the malignant transformation of solid tumors by enhancing cell proliferation, migration, and invasion. ASPH also promotes tumor growth by stimulation of angiogenesis and immunosuppression. These effects are mainly achieved via the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 103 publications
(174 reference statements)
0
55
0
Order By: Relevance
“…We constructed the risk signature using the 12 genes. Among them, aspartate β-hydroxylase (ASPH) plays a pivotal role in the malignant transformation of solid tumors by enhancing cell proliferation, migration, invasion and stimulation of angiogenesis, and immunosuppression (Ince et al, 2000;Huyan et al, 2014;Kanwal et al, 2020). A previous study showed that repression of aldehyde dehydrogenase 2 family (ALDH2) promotes lung tumor progression through accumulated acetaldehyde and DNA damage (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We constructed the risk signature using the 12 genes. Among them, aspartate β-hydroxylase (ASPH) plays a pivotal role in the malignant transformation of solid tumors by enhancing cell proliferation, migration, invasion and stimulation of angiogenesis, and immunosuppression (Ince et al, 2000;Huyan et al, 2014;Kanwal et al, 2020). A previous study showed that repression of aldehyde dehydrogenase 2 family (ALDH2) promotes lung tumor progression through accumulated acetaldehyde and DNA damage (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Further, considering the pleiotropic effects that NOG and its derivatives exhibit in cellular studies, application of related 2-oxo acid derivatives to cells may trigger phenotypes useful in identifying previously overlooked 2OG oxygenase/2OG-utilizing enzyme functions. FIH 76 and AspH 22 26 are proposed medicinal chemistry targets and the use of (partially) selective 2OG derivatives, such as 13 or corresponding esters in cellular studies may help to improve the currently limited understanding on their biochemical roles and complement similar approaches using heterocyclic small-molecules 24 , 76 81 .…”
Section: Discussionmentioning
confidence: 99%
“…S4C and S4D), suggesting INPP5F may affect the function of ASPH. Previous reports showed that the Notch pathway is a downstream signaling of ASPH [20,21]. Coincidentally, c-MYC and cyclin E1 are important targets of the Notch signaling pathway [22,23].…”
Section: Inpp5f Activates Notch Signaling Pathway Via Interacting With Asphmentioning
confidence: 97%